EFFECTS OF BUOYANCY PARAMETER ON UNSTEADY 3D DOUBLE DIFFUSIVE CONVECTION IN MOLTEN PB-SN ALLOYS - Chemseddine, Maatki; Öztop, Hakan Fehmi; Kolsi, Lioua; Al-Rashed, Abdullah A. A. A.; Borjini, Mohamed Naceur; Abu-Hamdeh, Nidal (Global Digital Central, 2017)
A computational study has been made for a three dimensional double diffusive convection with molten Pb-Sn by using finite volume method. In this work, two vertical walls have different temperature and different concentration while remaining walls are adiabatic. Buoyancy ratio, which changes between N = -0.1 and -10, is the main governing parameter during work. Other parameters are taken as fixed with Pr = 0.02, Le = 7500 and Ra = 5x10(3). It is found that changing of buoyancy parameter becomes more effective on heat transfer than that of mass transfer.
Keywords: double diffusive; natural convection; molten Pb-Sn; heat transfer; numeric